Prevalence of Depression in Older Nursing Home Residents in High and Low Altitude Regions: A Comparative Study - Wang, Fei; Liu, Shou; Zhang, Qinge; Ng, Chee H.; Cui, Xiling; Zhang, Dexing; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Objective: Depressive symptoms (depression hereafter) is common in older adults, and closely associated with environmental factors. This study compared the prevalence of depression in older adults living in high-altitude and low-altitude regions, and their association with quality of life (QOL). Method: A total of 632 older nursing home residents were included, with 425 participants living in low-altitude and 207 participants living in high-altitude regions. Depression and QOL were assessed using standardized instruments. Results: The prevalence of depression was 26.9% (95% CI: 23.43–30.37%) in the whole sample of older nursing home residents, with 11.1% (95% CI: 8.01–14.05%) in those living in low-altitude and 59.4% (95% CI: 52.68–66.17%) in those living in high-altitude regions. Multiple logistic regression analysis revealed that living in low-altitude region (P < 0.001, OR = 0.07, 95% CI: 0.04–0.12) was associated with lower risk of depression, while perception of poor health status (P < 0.001, OR = 3.86, 95% CI: 1.98–7.54) and having insomnia (P < 0.001, OR = 4.76, 95% CI: 2.99–7.56) were associated with higher risk of depression. QOL was significantly lower in physical (F(1,632) = 35.421, P < 0.001), psychological (F(1,632) = 20.777, P < 0.001), social (F(1,632) = 8.169, P < 0.001) and environmental domains (F(1,632) = 11.861, P < 0.001) in those with depression. Conclusion: Depression was common in older nursing home residents especially those living in the high-altitude region. Considering the negative impact of depression on QOL and functional outcomes, routine screening and timely treatment of depression should be implemented in this population.